The influence of the moisture content on the electrical resistance of two types of cork stoppers - Fernandez-Golfin, J.; Conde García, M.; González Hernández, F.; Conde García, M.; Fernadez-Golfin, J. J.; Baonza Merino, M. V.; García Esteban, L.; González Adrados, J. R. (Forest Systems, 2010)
The relationship between the log of the electrical resistance (ER; measured using pin electrodes) and the moisture content (MC) have not been reported in any form of cork. That is important for the cork stoppers industry because it should help in the design and verification of more precise devices for measuring cork moisture content. In this study, using linear regression techniques, different regression models of the type log(Log(R) + 1) = axh+b were derived to describe the relationship ERMC, that was measured using pin electrodes on two types of cork stoppers [natural (N) and agglomerate(AG)]. The results obtained show that in the models proposed, the moisture content of AG cork stoppers can be estimated with an error of ± 0.3%, while that of N stoppers can be estimated with an error of 0.5%. Neither the geographical origin of the N corks nor the surface treatment to which the AG corks were subjected significantly affected the proposed models.Therefore, the moisture content of cork stoppers could be measured at the industrial scale using electrical resistancetype moisture meters.